Transport in correlated open quantum systems - Talarico, N. Walter (fi=Turun yliopisto|en=University of Turku|, 2021)
The problem of the dynamics in open and correlated quantum systems has gained attention in recent years due to the impressive experimental advances that were made in quantum transport in molecular systems. The importance of understanding and controlling molecular electronic and quantum transport will soon lead to the realization of quantum technological devices that can be integrated in the present silicon-based technology to make better and faster circuitry. On a fundamental and theoretical level, one needs to take into account time-dependent processes where self-interactions within the parts of an atomic or nano-scale system and interactions with macroscopic external environments are the main cause for quantitative and qualitative changes on the physical and dynamical properties of the quantum system itself. This thesis aims at discussing the problem of transport in correlated open quantum systems by using the non-equilibrium Green’s function approach for describing in particular the effects of correlations in the charge and heat transport dynamics. Unfortunately, because of the unusual two-times structure of the integral formulation that characterized the theory, nowadays there are no commercial software available to carry out the calculations needed to find its solutions, and thus, dedicated software have to be self implemented and programmed. Hence, in the thesis, we first give an introduction of the overall structure of the theory and then a detailed explanation on how to numerically implement tools for several operations on the non-equilibrium Green’s functions, the construction of self-energies, and the solution of the integral equations. Furthermore, as the formalism allows for studying time-dependent transport in interacting and arbitrary nano-scale systems coupled to wide band and macroscopic leads, we present and discuss several applications when these systems are rapidly brought out-of-equilibrium with the application of electrical and thermal biases. More specifically, we theoretically investigate transport of correlations across quasi-crystalline structures and how charge and heat are carried along nanoscopic junctions that span from quantum dots, quantum nanowires and carbon nanotubes.

Avointen ja korreloituneiden kvanttisysteemien tutkimus on saanut viime vuosina paljon huomiota molekyylisysteemeissä tapahtuvan kvantti-kuljetuksen kokeellisten edistysaskelten ansiosta. Molekulaarisen sähkön- ja kvanttisiirron ymmärtämisen tärkeys on sellaisten kvanttiteknologioiden toteuttaminen, jotka voidaan integroida nykyisiin piipohjaisiin teknologioihin parempien ja nopeampien piirien tuottamiseksi. Perustavanlaatuisella ja teoreettisella tasolla on otettava huomioon aikariippuvia prosesseja, joissa sekä itseisvuorovaikutukset atomi- ja nanokokoisten systeemien sisällä että vuorovaikutukset makroskooppisten ympäristöjen kanssa ovat ensisijainen syy kvanttisysteemin fysikaalisten ja aikariippuvien ominaisuuksien laadullisiin ja määrällisiin muutoksiin. Tämä väitöskirja käsittelee korreloituneissa avoimissa kvanttisysteemeissä tapahtuvan kvantti-siirron problematiikkaa käyttäen hyödyksi epätasapaino Greenin funktioiden lähestymistapaa kuvaamaan erityisesti korrelaatioiden vaikutusta varaus- ja lämpösiirron aikakehityksessä. Valitettavasti teorian karakterisoivasta integraalimuotoilun kaksiaikarakenteesta johtuen nykyään ei ole tarjolla kaupallisia ohjelmistoja jotka pystyvät suorittamaan laskuja ratkaisujen löytämiseksi. Siksi tätä tarkoitusta varten täytyy itse ohjelmoida siihen räätälöityjä ohjelmistoja. Tästä syystä tämä väitöskirja esittelee ensin johdannon ja teorian pääpiirteisen rakenteen. Sen jälkeen käsitellään yksityiskohtaisesti, kuinka implementoida numeerisesti itseisenergiat, integraalimuotojen ratkaisut ja työkaluja useita operaatioita varten epätasapaino Greenin funktioille. Sen lisäksi formalismi mahdollistaa aikariippuvan siirron tutkimisen vuorovaikuttavissa ja mielivaltaisissa nanomittakaavan systeemeissä, jotka on kytketty makroskooppisiin ja laajan transmissiovyön johtimiin. Esittelemme ja käsittelemme useita sovelluksia, joissa nämä systeemit saatetaan nopeasti pois tasapainosta käyttäen sähkö- ja lämpö-vinoumaa. Tarkemmin sanottuna tutkimme teoreettisesti kuljetusa ja korrelaatioita kvasikiderakenteita pitkin ja kuinka varaus ja lämpö kulkeutuvat pitkin nanokokoisia